2017
DOI: 10.1038/pr.2017.146
|View full text |Cite
|
Sign up to set email alerts
|

Association of the gut microbiota mobilome with hospital location and birth weight in preterm infants

Abstract: BackgroundThe preterm infant gut microbiota is vulnerable to different biotic and abiotic factors. Although the development of this microbiota has been extensively studied, the mobilome-i.e. the mobile genetic elements (MGEs) in the gut microbiota-has not been considered. Therefore, the aim of this study was to investigate the association of the mobilome with birth weight and hospital location in the preterm infant gut microbiota.MethodsThe data set consists of fecal samples from 62 preterm infants with and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Although, there are several lines of bioinformatics evidence of extensive HGT in the human commensal gut microbiota, this has not yet been experimentally proven (3,4,(23)(24)(25). In the current work we have experimentally shown frequent transmission of MGE between gut associated bacteria, and laboratory strains.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although, there are several lines of bioinformatics evidence of extensive HGT in the human commensal gut microbiota, this has not yet been experimentally proven (3,4,(23)(24)(25). In the current work we have experimentally shown frequent transmission of MGE between gut associated bacteria, and laboratory strains.…”
Section: Discussionmentioning
confidence: 62%
“…Recent culture independent work has indicated high levels of horizontal gene transfer (HGT) in the human gut (3). This enables the potential for transmission of antibiotic resistance -(ARG) and virulence genes within the preterm infant gut microbiota (4).…”
Section: Introductionmentioning
confidence: 99%
“…ResFinder -Metagenomic read-mapping outperformed cultivation-based techniques in terms of predicting expected tetracycline resistance based on farm antimicrobial consumption Weinroth et al (2018) Bovine faecal samples during a clinical trial using ceftiofur and chlortetracycline MEGARes -Treatment with ceftiofur was not associated with changes in b-lactam resistance genes -Treatment with chlortetracycline had a significant increase in relative abundance of tetracycline resistance genes -There was an increase in resistance to an antimicrobial class not administered during the study, which is a possible indication of co-selection of resistance genes Munk et al (2018) Samples from pig and poultry farms ResFinder -Higher AMR gene loads were observed in pig farms, whereas poultry resistomes were more diverse -Several critical AMR genes, including mcr-1 and optrA, were detected, the abundance of which differed both between host species and between countries -The total acquired AMR genes level was associated with the overall country-specific antimicrobial usage in livestock The main advantages of shotgun metagenomics over classical methods for analysing the resistome is that this methodology is faster, allows for the simultaneous detection of a vast number of resistance genes of different microbial origins within a given sample and the estimation of their relative abundance, and in some cases it is possible to get important information on the genetic background of the detected AMR determinants (microbial species or strain of origin and/or association with mobile genetic elements, such as plasmids, integrons, transposons, prophages, etc.). In fact, shotgun metagenomics can be also used to characterise the so-called mobilome (pool of mobile genetic elements) in a given sample (Ravi et al, 2017). However, the attribution of the identified resistance genes to specific taxa or strains and their identification as transferable or non-transferable resistance determinants is not possible in most cases yet, which would hamper the assessment of the risk posed by such AMR determinants.…”
Section: Metagenomics In Food-borne Outbreak Detection/investigationmentioning
confidence: 99%
“…The reasons for these specific plasmid-host combinations remain elusive; however, we found that IncI and IncB/O plasmids displayed the highest in vitro conjugation efficiencies compared to other ESBL-encoding plasmids. Moreover, the IncB/O plasmid group was found to be the second most commonly identified plasmid group in commensal and pathogenic E. coli from humans and animals 75 , while the conjugative IncI group was can also be highly prevalent in commensal bacteria from infants 76 . The regular sampling of these plasmids by cipR S. sonnei could be attributed to several factors, including the close genetic relatedness between Shigella and E. coli , the propensity of S. sonnei to acquire AMR plasmids, and the circulation of highly transmissible AMR plasmids in commensal E. coli .…”
Section: Discussionmentioning
confidence: 99%